2018
DOI: 10.1002/pssr.201800485
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low‐Frequency Vibrations on Charge Transport in High‐Mobility Organic Semiconductors

Abstract: Despite decades of intensive studies of charge transport in organic semiconductors (OSs), understanding of mechanisms underpinning efficient charge transport in them remains elusive. Recently, it has been suggested that low‐frequency (LF) vibrations are a limiting factor of charge transport in high‐mobility OSs. Nevertheless, the relationship between the molecular structure, crystal packing, LF vibrations, and charge transport is still obscured. This hinders the focused search of high‐mobility OSs so that rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 125 publications
(289 reference statements)
0
10
0
Order By: Relevance
“…As mentioned above, LF Raman spectra are sensitive to the crystal structure and hence can monitor its changes. 46,56,57 Fig. 4 shows that the LF bands for CF 3 -PTzTzP-CF 3 have a considerably lower intensity than those for CF 3 -PTTP-CF 3 .…”
Section: Molecular and Crystal Structuresmentioning
confidence: 95%
See 2 more Smart Citations
“…As mentioned above, LF Raman spectra are sensitive to the crystal structure and hence can monitor its changes. 46,56,57 Fig. 4 shows that the LF bands for CF 3 -PTzTzP-CF 3 have a considerably lower intensity than those for CF 3 -PTTP-CF 3 .…”
Section: Molecular and Crystal Structuresmentioning
confidence: 95%
“…It was previously suggested that the LF Raman spectra are related to vibrational modulation of the charge transport integrals and the molecular polarizability: the more intense the LF Raman signal, the stronger this modulation. 46,58 Thus, the decrease in the LF Raman intensity can be attributed to a weaker impact of the corresponding vibrations on the charge transfer integrals between the molecules, i.e., the lower dynamic disorder. The latter is favorable for charge transport.…”
Section: Molecular and Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…5,23,[25][26][27][28] The anharmonic components of the lattice vibrations, i.e., phonon-phonon interactions 29 are therefore entirely neglected. However, organic crystals are known to be mechanically soft 30 , exhibit large molecular displacements 31 and have large thermal expansion coefficients 32 all of which are indicative of strong lattice anharmonicity. 33,34 Strongly anharmonic lattice dynamics are expected to have a disruptive effect on the electronic coupling between the molecules, and therefore they may profoundly impact charge transport in the organic crystal.…”
mentioning
confidence: 99%
“…21,22 The relationship between molecular structure, crystal packing, low-frequency vibrations and charge transport still poses many open questions and there would be significant value in developing a framework to design these materials. 23,24 We are particularly interested in chiral helicene molecules as potential OSCs. Helicenes are axially fused benzene rings, as shown for [6]helicene in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%